Civil and criminal liability for damage caused by self–driving cars - Rimkutė, Deimantė; Povylius, Kristijonas (Vilnius University Open Series, 2021)
The article aims to analyse and assess whether the existing legal regulation in Lithuania is sufficient for application of civil and criminal liability for damage caused by fully self–driving cars. This hypothesis is confirmed by analysing the technical specifics of fully self–driving cars, the legal regulation of civil and criminal liability in Lithuania and the main theories of these types of liability.
Keywords: self–driving car; artificial intelligence; criminal liability; civil liability